Sea Wave Height Monitoring Prototype as an Early Warning System for Tidal Flood Disaster - Samsul Muhayadi; I Wayan Sudiarta; Eko Pradjoko (Department of Physics, Sebelas Maret University, 2025)
Indonesia is an archipelagic country located between the Indian Ocean to the south and the Pacific Ocean to the north. As a consequence of this, during the rainy and transitional seasons, extreme weather occurs, especially in the southern coastal areas. According to data from the National Disaster Management Agency, in the last six years, more than 200 tidal waves and abrasion have hit the coastal areas of Indonesia. These conditions can lead to various disasters, particularly tidal flooding. Therefore, the development and design a wave height monitoring device as an early warning system for tidal flooding is necessary. This device is expected to play a vital role in disaster mitigation, because it can provide the information about the potential for tidal flooding based on the changes in wave height. The design of this device uses the LPD3806 encoder as a sensor and the nRF24L01 to send information to the monitoring station. Furthermore, running tests has been conducted and based on the results of the maximum distance test, information delivery can reach 800 meters in an open area with a maximum delay of 2 seconds. For sensor accuracy, a value of 99.7% was obtained, indicating the sensor has a small measurement error rate. On top of that, during field tests, the device demonstrated durability under bad weather, with no loss of data sent. This shows that this device can operate reliably under extreme weather environments.